Telaah Ma’anil Hadis Memilih Pasangan Hidup yang Mapan (Kasus Hadis Fathimah Binti Qais) - Sari, Fitria Mita; Febriyeni, Febriyeni (Institut Agama Islam Sumatera Barat, 2023)
Nowadays, an important criterion in choosing a life partner for women is wealth or stability, which is the main capital for household. Women who put the criteria for stability are often referred to as matre, everything that only looks at money and material, even though realistically women need the lives of themselves and their children later so that they are not lacking. As in the case of the Hadith of Fatimah bint Qais, the Prophet SAW recommended Fatimah not to choose a poor man and choose an established man. This research uses the hadith analysis method, with textual and contextual approaches. Based on the analysis of the hadith of choosing a well-established life partner from a textual point of view, poverty means the inability to meet the needs of livelihood and not having property. From the contextual point of view, seen from the asbabul wurud and its purpose, Fatimah bint Qais was a noble daughter whose standard of living was sufficient and did not match the life of Mu'awiyah bin Abu Sufyan who was difficult and poor, especially in terms of maintenance. Rasulullah chose Usamah bin Zaid as Fatimah's husband because of the advantages and compatibility, so that a household life that is sakinah, mawaddah and rahmah is achieved when married to Usamah. The stability in question is the ability of a man to be responsible for meeting all his needs with sufficient financial life. Well-established does not mean having to be rich, but stable life and no economic shortcomings.